[Identification of Distinct Amino Acid Composition of Human Cruciform Binding Proteins] - Bartas, М; Bažantová, P; Brázda, V; Liao, J С; Červeň, J; Pečinka, P (Molekuljarnaja biologija, 2019)
Cruciform structures are preferential targets for many architectural and regulatory proteins, as well as a number of DNA binding proteins with weak sequence specificity. Some of these proteins are also capable of inducing the formation of cruciform structures upon DNA binding. In this paper we analyzed the amino acid composition of eighteen cruciform binding proteins of Homo sapiens. Comparison with general amino acid frequencies in all human proteins revealed unique differences, with notable enrichment for lysine and serine and/or depletion for alanine, glycine, glutamine, arginine, tyrosine and tryptophan residues. Based on bootstrap resampling and fuzzy cluster analysis, multiple molecular mechanisms of interaction with cruciform DNA structures could be suggested, including those involved in DNA repair, transcription and chromatin regulation. The proteins DEK, HMGB1 and TOP1 in particular formed a very distinctive group. Nonetheless, a strong interaction network connecting nearly all the cruciform binding proteins studied was demonstrated. Data reported here will be very useful for future prediction of new cruciform binding proteins or even construction of predictive tool/web-based application.
Keywords: proteiny vázající poly-ADP-ribosu; DNA-Binding Proteins; Humans; chromozomální proteiny, nehistonové; DNA Topoisomerases, Type I; DNA vazebné proteiny; HMGB1 Protein; Poly-ADP-Ribose Binding Proteins; DNA-topoisomerasy I; chromatin; lidé; aminokyseliny; protein HMGB1; Amino Acids; Chromatin; Chromosomal Proteins, Non-Histone; konformace nukleové kyseliny; onkogenní proteiny; Nucleic Acid Conformation; Oncogene Proteins